Application of enthalpy formulations for numerical simulation of castings solidification - Sczygiol, Norbert; Szwarc, Grzegorz (Computer Assisted Methods in Engineering and Science, 2023)
The paper deals with a numerical modelling of solidification in which enthalpy formulations were used. The finite element method (FEM) was applied for computer simulation of solidification. This is the most common numerical method used in the simulation of physical processes. The enthalpy formulations are more convenient to use than temperature formulations in the multidimensional problems in which FEM is applied. The paper concentrated on two enthalpy formulations: the apparent heat capacity formulation and the basic enthalpy formulation. The time integration schemes and the numerical realisation of boundary conditions were discussed. The models of solid phase growth and the implementation details used in this paper were shown in work [15]. The presented results of computer simulations contain: temperature fields, solidification kinetics, cooling velocities and calculated distributions of equiaxed grain size.